Prevalencia de terceros molares y caninos impactados, retenidos o incluidos en las radiografías panorámicas de las historias clínicas de la Universidad Antonio Nariño de Bucaramanga de los años 2019 a 2022 - Álvarez Gutiérrez, Jhon Ferney; Gutiérrez Vélez, Mayra Alejandra; Parra Acosta, Álvaro Javier (Universidad Antonio Nariño, 2024)
Introduction: Inclusion, retention, and impaction are alterations in the oral cavity where teeth do not undergo conventional eruption, resulting in an abnormal position in the alveolar bone and potentially causing local complications in oral health.